Tracheostomy in Laryngeal Tumor Patients with Grade III Upper Airway Obstruction: A Case Report - Irbah Nabila Aprilia; Fivien Fedriani (Indonesian Journal of Global Health Research, 2023)
The larynx is an organ that has a central role in coordinating the functions of the upper respiratory tract including respiration, speaking and swallowing. The larynx is divided into the supraglottis, glottis and subglottis. Laryngeal tumors are divided into 2 there are benign tumors where the most common is laryngeal papilloma and malignant tumors of the larynx which the most common is squamous cell carcinoma. Cases of laryngeal carcinoma often have complications of airway obstruction and require early and emergency treatment. Laryngeal obstruction requires special attention because the larynx is a narrow area of the upper airway. This study is a case report that observed patients with laryngeal tumors from before surgery to after surgery. The aim of this study was to determine the results of tracheostomy treatment in patients with laryngeal tumors. Airway obstruction can create shortness of breath due to airway obstruction which can be total or partial. This case report discusses Mr. S is 44 years old who has complained of shortness of breath since 3 days before entering the hospital. The patient also complained of a hoarse voice, sore throat, and a feeling of something being stuck since 7 months ago. The patient has also been an active smoker since he was 15 years old and has been drinking alcohol. The patient was finally diagnosed with well-differentiated squamous cell carcinoma of the larynx with OSNA grade III based on anamnesis, physical examination, and investigations. The patient underwent a tracheostomy to resolve airway obstruction and a microlaryngeal biopsy to confirm the diagnosis of carcinoma. After obtaining the results of the patient's anatomic pathology that the patient had laryngeal carcinoma, the action taken was a total laryngectomy.